Managing business networks for value creation in facilities and their external environments: A study on co-location. Issue 1 (7th February 2017) - Artto, Karlos; Ahola, Tuomas; Kyrö, Riikka; Peltokorpi, Antti
Abstract : Purpose: The purpose of this paper is to increase understanding of the logic of business network formation among the co-located and external actors of a facility. Design/methodology/approach: The research adopts a theory-building approach through developing propositions inductively from the empirical case study on four purposefully sampled modern service station facilities. The focus is on analyzing how a facility and its inherent co-located actors represent an entity that forms a business network with external actors in the facility's environment. Findings: The findings propose that when co-located with a large number of actors, the facility and its actors represent an entity that is connected to a wide business network of multiple external actors. On the other hand, when co-located with a small number of actors, the facility becomes a part of the overall supply in the surrounding business environment with a differentiated offering for competitive advantage. Practical implications: The research suggests that an appropriate co-locating strategy, for example, when planning the tenant mix of the facility, can contribute to creating a vivid business network in the external environment, which raises the facility to a role of a central entity in such a network. Originality/value: The findings explaining how co-location affects the businesses within the facility and within a wider networked environment are novel to the scholarly knowledge on co-location. The research bridges the theories of co-location and business networks that have been treated as separate discourses in previous research.